Implementation of a Suicide Risk Screening Instrument in a Remand Prison Service in Berlin - Dezsö, Dora; Konrad, Norbert; Seewald, Katharina; Opitz-Welke, Annette (Frontiers in Psychiatry, 2018)
In the present study, we examined the effects of implementing a suicide risk screening instrument in a pre-trial detention facility for men in Berlin. Within a period of 3 months, all newly arriving prisoners were screened by social workers or prison officers. Cases of elevated suicide risk were immediately referred to psychological or medical service personnel the same day. Follow-up over a 6-month period showed that 14% of all incoming prisoners were classified as high-risk individuals. These individuals received significantly more psychological and psychiatric treatment and were significantly more likely to be accommodated in crisis intervention rooms and emergency communities such as shared prison cells. In addition, it was found that despite the increased amount of treatment in the high-risk group, the number of specific measures did not increase significantly compared to the pre-implementation phase.